Intrapartum magnesium sulfate and need for intensive delivery room resuscitation. Issue 1 (17th September 2014) - Weisz, Dany E; Shivananda, Sandesh; Asztalos, Elizabeth; Yee, Wendy; Synnes, Anne; Lee, Shoo K; Shah, Prakesh S
Abstract : Objective: To evaluate the association of intrapartum magnesium sulfate for fetal neuroprotection (MgSO4 -FN) with the delivery room resuscitation and neonatal outcomes of preterm infants in an era of minimisation of invasive mechanical ventilation. Design: Retrospective cohort study. Setting: Neonatal intensive care units in the Canadian Neonatal Network. Patients and intervention: Preterm infants (23 0 to 31 6 weeks gestational age) born in 2011 or 2012. Resuscitation requirements and neonatal outcomes were compared between infants exposed and unexposed to intrapartum MgSO4 -FN. Main outcome measures: The primary outcome was a composite outcome of 'intensive resuscitation', defined as the need for intubation and ventilation or chest compressions or epinephrine administration in the delivery room. Secondary outcomes included mortality and major neonatal morbidities. Results: Of 6015 eligible infants, 1387 (23.1%) were exposed to intrapartum MgSO4 -FN. Significantly fewer MgSO4 -FN infants (41.0% vs 44.6%, p=0.02) required intensive resuscitation. However, after adjustment for confounders, this difference was no longer significant (adjusted OR (AOR) 0.88; 95% CI 0.66 to 1.17). Infants exposed to MgSO4 -FN had decreased odds of death (AOR 0.61; 95% CI 0.40 to 0.94), but there was no difference in neonatal morbidities compared with the unexposed infants. Conclusions: Intrapartum MgSO4 for fetal neuroprotection was not associated with an increased need for intensive delivery room resuscitation in this cohort of preterm infants.